De-commemoration of an urban street in Egypt: the case of Gameat-Aldowel-Alarabyia street. (15th July 2019) - Abdelwahab, Mona A.
Abstract : Purpose: The purpose of this paper is to explore the "event" of the construction of Naguib Mahfouz Square. Drawing on the memory of Gamaet-Aldowel-AlArabyia Street, it attempts to uncover the socio-cultural structures inherited in the Egyptian urban street. Design/methodology/approach: This study adopts Foucauldian discourse on institutions of "knowledge and authority" to approach the power relations between the actors involved. This discourse was constructed through in-depth, unstructured interviews with architects and involved government personnel as well as other archival resources that included national newspapers and magazines. Findings: This discourse reflected an institutional controversy between these actors over the perception and design of the Egyptian street, highlighting the alienation of the designer, and the user/lay-people, from the urban institution. Naguib Mahfouz Square presented a considerable deviation from the established norms of street design in Egypt at that time through its commemoration of a contemporary figure in literature, the architect's involvement in the design process and the unfencing of urban space. This event thus questions the perception of the urban street beyond our socio-cultural inheritance, and towards street design as a performative urban act that embraces the everyday activities of lay-people in the street. Originality/value: The paper utilises Foucauldian discourse on power to approach a case study of an urban event and space in Egypt, which has not previously been investigated thoroughly. It thus holds potential towards the resolution of inherited conflict between the urban street and the urban institution.